The Influence Of Total Quality Management And Management Accounting Information Systems On Managerial Performance In Hotel Companies In Palembang City - Jonnie, Narada Ellysia; Panjaitan, Delfi (Prodi Akuntasi, Fakultas Bisnis dan Akuntansi Unika Musi Charitas, 2023)
This study aims to determine the effect of total quality management and management accounting information systems on managerial performance in hotel companies in Palembang City. The theory used in this research is Resource Based View. The data used is primary data. The population in this study were all 3 to 5 star category hotels registered with the Regional Tax Management Agency (BPPD) of Palembang City. The sampling technique used was purposive sampling method and obtained 23 companies with a total of 52 samples. Hypothesis testing is done by using multiple linear regression analysis. The results of this study indicate that total quality management has a significant positive effect on managerial performance, and management accounting information systems have a significant positive effect on managerial performance.